From reality to the stage. Vulnerability and political potency in testimonial theatre - López Francia, Diego (2022)
Vulnerability is a fundamental component of Performing Arts. The body performing “here and now” is constantly at risk of realising what has been prepared in rehearsals, in addition to being exposed to the gaze and judgement of the audience. In Testimonial Theatre -which presents real people, testimonies, and documents- the performer’s vulnerability acquires another dimension, as the performer presents his/ her/their own story instead of representing a character. This passage from reality to the stage, which can be understood as an act of “taking off the mask”, generates a direct identification with the audience, which reveals the high potential of the political impact of Testimonial Theatre. Thus, taking the play Padre Nuestro as a case study, this article explores the relationship between vulnerability and political power in the creative process and outcome of a testimonial play through a philosophical-performative analysis of the passage from the “reality’s self ” to the “stage’s self ”.